Oxypeucedanin hydrate monoacetate isolated from Angelica dahurica induces apoptosis in Caco-2 colon carcinoma cells through the mediation of PI3K-signalling pathway and inhibition of cancer cell migration - Liu, Yu; Peng, Tian-Shu; Hu, Xiang-Dang; Li, Shuai-Jun; He, Yong-Heng; Hu, Fan; Jiang, Jinbo (Bangladesh Journal of Pharmacology, 2016)
The main aim of the present research work was to demonstrate the antitumor and apoptotic activities of oxypeucedanin hydrate monoacetate isolated from Angelica dahurica against Caco-2 colon cancer cells. MTT cell viability assay along with clonogenic assays were used to study the effect of the compound on cell cytotoxicity and the colony forming tendency. Fluorescence microscopy using acridine orange/ethidium bromide was used to study the effects on apoptosis. In vitro wound healing assay and Western blotting were carried out to study effect on cell migration and PI3K-signalling pathway. The results revealed that oxypeucedanin hydrate monoacetate inhibited Caco-2 cell proliferation and decreased the number of cancer colony forming cells. This compound exerted anti-migratory effects in dose- and time-dependent manner. As compared to the untreated control, drug-treated cells showed significant inhibition of cancer cell migration. Oxypeucedanin hydrate monoacetate significantly down-regulated the expression of pAkt and pPI3K in Caco-2 cells.